Sensitive and Accurate Determination of Copper in Blood and Urine Samples by Vortex-assisted Dispersive Liquid-liquid Microextraction-slotted Quartz Tube - Flame Atomic Absorption Spectrometry After Complexation with a Novel Schiff-base Ligand - Bakirdere, Emine Gulhan; Maltepe, Esra (ATOMIC SPECTROSCOPY PRESS LTD, 2019)
Due to the low sensitivity of flame atomic absorption spectrometry for trace copper determination, dispersive liquid-liquid microextraction and slotted quartz tube were used to increase the instrument's detection power by about 102-fold. This high detection improvement was achieved by performing a comprehensive optimization study on the microextraction method and slotted quartz tube parameters. A novel ligand was used to form the copper complex prior to the extraction process. The limits of detection and quantification obtained under optimum experimental conditions were 0.52 and 1.7 ng/mL, respectively. The calibration plot was linear over a wide concentration range, and the percent relative standard deviation of the lowest concentration in the linear calibration plot was less than 5.0%, indicating high precision for the extraction procedure and instrumental measurements. In order to determine the validity and applicability of the developed method, recovery studies were carried out on blood and urine samples at different spiked concentrations. The recovery results recorded for both samples ranged between 85% and 113% which confirmed that the method can be applied to these matrices with high accuracy and precision.
Keywords: WATER SAMPLES; IONIC LIQUID; DROP MICROEXTRACTION; TRACE LEVELS; PRECONCENTRATION; CADMIUM; LEAD; FOOD; Spectroscopy